Gaming behaviors among young people with visual impairment. (30th September 2020) - Wrzesinska, M; Tabała, K; Stecz, P
Abstract: It has been reported that 60% of young people with visual impairment (VI) enjoy playing digital games (DGS) on the computer. However, little is still known about the new media patterns among young people with special needs. Hence, the aim of this study was to identify gaming behaviors among students with VI. A self-administered questionnaire assessing variables regarding gaming behaviors adapted for students with special needs was prepared. Finally, 490 Polish respondents with VI from 9 special schools aged 13-24 (17.9 ± 2.48) were included. Purposive sampling was chosen during selection of the members of the population. Almost 84% of students with VI had experience in playing DGs. Poor-sighted students were significantly more likely to be players than those who were blind (89% vs 11%; χ2 =22.471; P< .001). More male (57.1%) than female students (42.9%) reported playing DGs (χ2=17.913; P <.001). Students with siblings were more likely to play DGs than those without and they were more likely to play computer games if they lived with a parent whose education was at primary/secondary level (χ 2=7.340; P= .025) The most commonly chosen game genre was strategic (57.1%), whereas war games (37.7%) were less popular. Over 12% of the students took part in gaming sessions lasting 5 or more hours per day and the male students were 5.5 times more likely to report an excessive gaming than the female students (P=.000). The survey indicated a tendency towards excessive gaming in a significant proportion of young persons with VI. Sociodemographic variables are important in predicting gaming behaviors in this group and they should be taken into consideration in the future preventive actions to reduce the risk of behavioral addiction. Key messages: Young people with VI are the regular users of games and they also tend to have a high tendency to an excessive gaming. Sociodemographic variables are important factor to be taken in account when predicting gaming behaviors among people with VI.